1996
DOI: 10.1152/jappl.1996.80.6.2204
|View full text |Cite
|
Sign up to set email alerts
|

Increased arterial desaturation in trained cyclists during maximal exercise at 580 m altitude

Abstract: This study utilized a hypobaric chamber to compare the effects of mild hypobaria (MH; 50 mmHg, approximately 580 m altitude) on blood O2 status and maximal O2 consumption (VO2max) in 9 untrained and 11 trained (T) cyclists with VO2max values of 51 +/- 3 and 77 +/- 1 ml.kg-1.min-1, respectively. In both groups, arterial O2 saturation (SaO2) decreased significantly during maximal exercise, and this effect was enhanced with MH. Both these responses were significantly greater in the T cyclists in whom the final Sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
114
1
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(125 citation statements)
references
References 0 publications
8
114
1
2
Order By: Relevance
“…Since Stanescu et al [1] did not measure blood gases in their experiments, however, we determined Pa O 2 , Pa CO 2 , and pH during control and ujjai respiration at a frequency of once per minute to account for lower chemosensitivity to CO 2 in the professional yogi. It has hitherto been reported that blood gases do not change much with physical exercise under a moderate workload, but average arterial pH decreased to 7.24 and Pa O 2 decreased to 68.3 torr at exhaustion during maximal exercise in the trained cyclists [14]. In the present study, the average values (ϮSD) of Pa O 2 , Pa CO 2 , Sa O 2 , and pH of 3 samplings during control breathing were 95.0 (Ϯ2.4) torr, 40.0 (Ϯ1.1) torr, 97.0 (Ϯ0.25)%, and 7.393 (Ϯ0.008), respectively.…”
mentioning
confidence: 80%
“…Since Stanescu et al [1] did not measure blood gases in their experiments, however, we determined Pa O 2 , Pa CO 2 , and pH during control and ujjai respiration at a frequency of once per minute to account for lower chemosensitivity to CO 2 in the professional yogi. It has hitherto been reported that blood gases do not change much with physical exercise under a moderate workload, but average arterial pH decreased to 7.24 and Pa O 2 decreased to 68.3 torr at exhaustion during maximal exercise in the trained cyclists [14]. In the present study, the average values (ϮSD) of Pa O 2 , Pa CO 2 , Sa O 2 , and pH of 3 samplings during control breathing were 95.0 (Ϯ2.4) torr, 40.0 (Ϯ1.1) torr, 97.0 (Ϯ0.25)%, and 7.393 (Ϯ0.008), respectively.…”
mentioning
confidence: 80%
“…In particular, the maximal aerobic workload (Ẇ max ) that can be sustained during exercise involving large muscle groups (e.g., cycling) is considerably lower in hypoxia compared with normoxia. The difference between these two environmental conditions increases progressively with the reduction in oxygen inspiratory pressure (PI O 2 ) (36) and is affected by subjects' fitness so that subjects with elevated maximal aerobic capacity are more affected by hypoxia (41).…”
mentioning
confidence: 99%
“…In fact, if any difference were to be expected, it would be the opposite. A review of the literature shows that highly trained (elite) individuals are more likely to show lower levels of Sao 2 , compared to untrained controls (Nielsen, 2003), and even at altitudes as low as 580 m endurance-trained athletes have been found to have increased desaturations at maximal exercise (Gore et al, 1996).…”
Section: Submaximal Saomentioning
confidence: 99%